Avaliação do Curso de Formação Técnica de Agentes Comunitários de Saúde da Escola de Saúde Pública do Ceará por meio da Política Nacional de Educação Permanente em Saúde no município de Horizonte - Moreira, Camila Mascarenhas (2022)
The National Policy of Continuing Education in Health (PNEPS) is an ethical-political-pedagogical proposal that aims to transform and qualify the practices of health care services, their training processes, and the model of health education, in addition to encouraging the organization of actions and services in an intersectoral perspective. Health promotion is the hallmark of the work of Primary Health Care, and the Community Health Workers (CHW) is the professional who should deal more with health promotion care than with healing procedures, whose vocation is born from a broad conception of health. Given the need for qualification and the specificities of this professional category, the Public Health School of Ceará proposed the technical training of CHWs, not only as an update of content, since the training began in 2005, but also as a methodological renewal based on the principles of PNEPS. In this context, the objective of this research is to evaluate the National Policy of Continuing Education in Health as a training tool for Community Health Workers through the implementation of the work processes presented by the Technical Course for Community Health Workers. This is evaluative research of qualitative approach, which falls within a counter-hegemonic perspective of evaluation with inspiration in the Evaluation in Depth and the Fourth Generation Evaluation, in which we sought to emphasize the subjective experience of the actors of the policy within the delineation of the dimensions of content, context, trajectory, and experience. It was carried out in the municipality of Horizonte, Ceará, with three groups of professionals (nurses, CHWs and managers) and the participation of the community. Notes were used in a field diary and semi-structured interviews established through the hermeneutic-dialectic circle. For data analysis, the Thematic Content Analysis was used. As results, the research experience points to the consolidation of the improvement of practices and the construction and strengthening of the bond between the teams. These elements have converged to increase the financing of Primary Care in the municipality and have expanded the scope of professionals with the development of skills inscribed in the relevance of learning new practices in health promotion..